Cadaveric comparison of the optimal site for needle decompression of tension pneumothorax by prehospital care providers. Issue 6 (December 2015) - Inaba, Kenji; Karamanos, Efstathios; Skiada, Dimitra; Grabo, Daniel; Hammer, Peter; Martin, Matthew; Sullivan, Maura; Eckstein, Marc; Demetriades, Demetrios
Abstract : BACKGROUND: Computed tomographic and cadaveric studies have demonstrated needle decompression of tension pneumothorax at the fifth intercostal space (ICS), anterior axillary line (AAL) has advantages over the second ICS midclavicular line (MCL). The purpose of this study was to compare the ability of prehospital care providers to accurately decompress the chest at these two locations. METHODS: Randomly selected US Navy hospital corpsmen (n = 25) underwent a standardized training session followed by timed needle decompression on unmarked fresh cadavers. A 14-gauge angiocatheter was inserted in the right and left second ICS MCL and fifth ICS AAL in a predetermined computer-generated order. Time from needle uncapping to insertion, accuracy, and ease of placement were examined. RESULTS: A total of 25 corpsmen inserted 100 needles into 25 cadavers. Mean (SD) age was 25.9 (3.7) years, 72.0% were male, with 4.2 (3.2) years of experience, and 52.0% had previously deployed. A total of 60.0% had attempted decompression previously, 93.3% in a model and 6.7% in a patient. Time to decompression did not differ between the second and fifth ICS (16.8 [10.1] seconds vs. 16.9 [12.3] seconds, p = 0.438). Accuracy however was superior at the fifth ICS, with a misplacement rate of only 22.0% versus 82.0% at the second ICS ( p < 0.001). The aggregate distance from the target position was also significantly greater for the second ICS (3.1 [1.7] cm vs. 1.2 [1.5] cm, p < 0.001). Insertion at the fifth ICS was rated as being easier than the second by 76.0% of providers, the same by 12.0%, and more difficult by 12.0%. CONCLUSION: For prehospital care providers, the fifth ICS AAL can be localized and decompressed with a higher degree of accuracy than the traditional second ICS MCL. It is rated as easier to perform and can be done just as quickly. Based on these data, the fifth ICS AAL should be considered as an equivalent first-line position for needle decompression in patients with clinical evidence of a tension pneumothorax.